2002
DOI: 10.1152/jn.2002.88.2.847
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Analysis of Synaptic Transmission in Central Neurons ofDrosophilaLarvae

Abstract: We report functional neuronal and synaptic transmission properties in Drosophila CNS neurons. Whole cell current- and voltage-clamp recordings were made from dorsally positioned neurons in the larval ventral nerve cord. Comparison of neuronal Green Fluorescent Protein markers and intracellular dye labeling revealed that recorded cells consisted primarily of identified motor neurons. Neurons had resting potentials of -50 to -60 mV and fired repetitive action potentials (APs) in response to depolarizing current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 70 publications
(50 reference statements)
9
106
0
Order By: Relevance
“…Note that glutamate signaling in the fly CNS differs from vertebrates due to the presence of inhibitory glutamate receptors. Previous studies have shown that motor neurons express glutamate-gated chloride channels (Rohrbough and Broadie 2002), which have been characterized in other invertebrates such as C. elegans (Vassilatis et al, 1997) but are absent from vertebrate genomes (Wolstenholme, 2012). The Drosophila homolog of this receptor, GluCl-alpha, produces a glutamate-gated chloride current when cloned and expressed in Xenopus oocytes (Cully et al, 1996).…”
Section: Looper-to-motor Neuron Connections Are Mediated By Glutamatementioning
confidence: 99%
“…Note that glutamate signaling in the fly CNS differs from vertebrates due to the presence of inhibitory glutamate receptors. Previous studies have shown that motor neurons express glutamate-gated chloride channels (Rohrbough and Broadie 2002), which have been characterized in other invertebrates such as C. elegans (Vassilatis et al, 1997) but are absent from vertebrate genomes (Wolstenholme, 2012). The Drosophila homolog of this receptor, GluCl-alpha, produces a glutamate-gated chloride current when cloned and expressed in Xenopus oocytes (Cully et al, 1996).…”
Section: Looper-to-motor Neuron Connections Are Mediated By Glutamatementioning
confidence: 99%
“…These motor neurons exhibit large excitatory synaptic currents, termed SRCs (Rohrbough and Broadie, 2002), between 10 and 15 times every minute (Fig. 5 A, B) (Baines et al, 2002).…”
Section: Synaptic Excitation Of Motor Neurons Is Reduced In Eaat1 Mutmentioning
confidence: 99%
“…Behavioral studies in the fruit fly Drosophila melanogaster, using an extensive library of mutant and transgenic animals, have resulted in identification of a number of genes and signal cascades that contribute to memory formation (Davis, 2004). In addition, physiological recordings in Drosophila, at the neuromuscular junction, from neurons in primary culture and in the CNS of embryos and larvae, have expanded our understanding of the molecular mechanisms regulating synaptic plasticity and neuronal excitability (Zhong and Wu, 1991;Broadie et al, 1997;Lee and O'Dowd, 2000;Renger et al, 2000;Yao and Wu, 2001;Hodges et al, 2002;Park et al, 2002;Rohrbough and Broadie, 2002;Baines, 2003;Hou et al, 2003;Rohrbough et al, 2003). However, limited electrophysiological access to neurons in central circuits in the adult fly has precluded exploration of the direct cellular links that mediate the translation of changes in gene expression to memory formation.…”
Section: Introductionmentioning
confidence: 99%